Rio Grande do Norte: interações urbanas e os centros de gestão do território - Paz, Diego Tenório da (2013)
The state of Rio Grande do Norte has been undergoing transformations in their territory, they are promoted by the installation of new infrastructure equipment, which in turn cause changes in the dynamic spatial and social hour set, causing new arrangements and new dynamics between cities. The overall goal of the research is to understand, at present, the urban network of the Rio Grande do Norte, from the centers of territory management. The picture presented in the paper reveals a network of cities that has gained a material basis urban, with the installation of new objects macro state structures (roads, ports, wind farms, banks, pipelines, internet access) that enable a relationship more intense between the urban centers of the state and other cities in the world, that the current structure characteristic of the urban network, its global nature, since the possibility of relations between the centers is greater. Such a relationship is indeed possible because the characteristics of the current historical period, with the high density of the tripod technique, science and information controlled by the market. In Rio Grande do Norte intentionality of the new arrangement that is configured is not other but meet market demands